Persona studies: Mapping the proliferation of the public self. (February 2014) - Marshall, P David
Celebrity has developed into a particularly powerful and pervasive trope for contemporary culture. It works at organising what we perceive as significant and this is made evident through its permeation of what constitutes news. Similarly, celebrity has been well documented in terms of its capacity to shape our entertainment: stardom is at least one of the cultural economies in which our stories and fictions are selected or read and recreated in popular culture. This article argues for the development of persona studies, where research on the celebrity is a subset of a wider study of how the self and public intersect and produce versions and identities that in some way continue to support the wider demands of our work economies.